2016
DOI: 10.1364/boe.7.005092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transfer function, resolution and depth of field of a soft X-ray microscope applied to tomography enhancement by Wiener deconvolution

Abstract: Full field soft X-ray microscopy is becoming a powerful imaging technique to analyze whole cells preserved under cryo conditions. Images obtained in these X-ray microscopes can be combined by tomographic reconstruction to quantitatively estimate the three-dimensional (3D) distribution of absorption coefficients inside the cell. The impulse response of an imaging system is one of the factors that limits the quality of the X-ray microscope reconstructions. The main goal of this work is to experimentally measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…The cryo vitrification of the cell will, in addition to preserving native structures, also drastically diminish radiation damage 15 . The sample is situated in a specimen grid used for electron microscopy so it can be transferred and precisely located at a different X-ray beamline designed for the second method: cryo X-ray fluorescence (XF) imaging.
Figure 4( A ) Principles of the soft X-ray microscope, operated at 520 eV in the so-called “water window” range 19 . Soft X-ray projection images are obtained in one-degree consecutive steps for an angular range up to 131 degrees.
…”
Section: Correlative X-ray Imagingmentioning
confidence: 99%
“…The cryo vitrification of the cell will, in addition to preserving native structures, also drastically diminish radiation damage 15 . The sample is situated in a specimen grid used for electron microscopy so it can be transferred and precisely located at a different X-ray beamline designed for the second method: cryo X-ray fluorescence (XF) imaging.
Figure 4( A ) Principles of the soft X-ray microscope, operated at 520 eV in the so-called “water window” range 19 . Soft X-ray projection images are obtained in one-degree consecutive steps for an angular range up to 131 degrees.
…”
Section: Correlative X-ray Imagingmentioning
confidence: 99%
“…However, the experimental characterization of both FZPs used at the Mistral microscope show a response that differs from ideal19. Although theoretical designs resulted in a totally incoherent and partially coherent regimes for ZP40 and ZP25, respectively, experimental characterization of the optical system for each scheme showed that the effective illumination pattern lead to a lower effective numerical aperture of the condenser (and, therefore, a greater degree of coherence), resulting in a Rayleigh resolution of 61.9 and 51.8 nm and DOF of 3.3 and 1.6 μm for ZP40 and ZP25, respectively19. Thus, for a more realistic validation we also computed tomogram simulations considering 3D PSF distributions numerically calculated to match both DOF and resolution for each experimental ZP.…”
Section: Resultsmentioning
confidence: 98%
“…Note that current tomographic acquisition schemes would employ a single tilt series, recorded such that the plane of best focus is at the specimen center (focal shift = 0). For purposes of comparison, we will refer to the tomogram obtained using standard reconstruction algorithms as 0-shift and when projections have been blurring corrected by deconvolution as 0-shift-dec 19. Similarly, we will refer as XTEND tomogram to the one derived from the combination of the tilt series at different defoci, following the workflow described in this work (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations